2011
DOI: 10.1261/rna.2775511
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-Seq reveals cocaine-regulated expression of striatal microRNAs

Abstract: MicroRNAs (miRNAs) are small RNAs that modulate gene expression by binding target mRNAs. The hundreds of miRNAs expressed in the brain are critical for synaptic development and plasticity. Drugs of abuse cause lasting changes in the limbic regions of the brain that process reward, and addiction is viewed as a form of aberrant neuroplasticity. Using next-generation sequencing, we cataloged miRNA expression in the nucleus accumbens and at striatal synapses in control and chronically cocainetreated mice. We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
139
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(147 citation statements)
references
References 66 publications
(92 reference statements)
7
139
0
1
Order By: Relevance
“…Next generation sequencing recently identified tens of miRNAs that are altered in NAc whole extracts and in purified striatal postsynaptic densities after chronic cocaine 166 . Among these, cocaine increased expression of miR-181a and decreased expression of miR-124 and let-7d in rat striatum 126; 167; 168; 169; 170 .…”
Section: Epigenetics and Addictionmentioning
confidence: 99%
“…Next generation sequencing recently identified tens of miRNAs that are altered in NAc whole extracts and in purified striatal postsynaptic densities after chronic cocaine 166 . Among these, cocaine increased expression of miR-181a and decreased expression of miR-124 and let-7d in rat striatum 126; 167; 168; 169; 170 .…”
Section: Epigenetics and Addictionmentioning
confidence: 99%
“…Several genes implicated in addiction models such as ΔFosB, dopamine transporter, and glutamate receptor subunits, have also been related to drug-triggered alterations in specific miRNAs [26]. Moreover, miRNAs are altered in NAc after chronic cocaine use [27]. However, extensive researches on miRNA affected by chronic substance intake and its relationship have yet to be elucidated.…”
Section: Histone Modificationmentioning
confidence: 99%
“…Finally, next-generation miRNA sequencing, microRNA-Seq, was used to identify cocaine-regulated miRNAs in the nucleus accumbens and striatal synapses. A number of miRNAs were identified that exhibit cocaine-induced expression changes, such as the miR-8 family members miR-429 and miR-200a/b (Eipper-Mains et al 2011). miRNAs are also involved in modulating brain physiology underlying alcohol addiction. In the adult mammalian brain, alcohol exposure rapidly up-regulates miR-9 expression levels in the striatum and supraoptic nucleus (SON).…”
Section: Micrornas In Drug Addictionmentioning
confidence: 99%